Hidden in plain sight: migration routes of the elusive Anadyr bar‐tailed godwit revealed by satellite tracking. (16th June 2022) - Chan, Ying‐Chi; Tibbitts, T. Lee; Dorofeev, Dmitry; Hassell, Chris J.; Piersma, Theunis
Abstract : Satellite and GPS tracking technology continues to reveal new migration patterns of birds which enables comparative studies of migration strategies and distributional information useful in conservation. Bar‐tailed godwits in the East Asian–Australasian Flyway Limosa lapponica baueri and L. l. menzbieri are known for their long non‐stop flights, however these populations are in steep decline. A third subspecies in this flyway, L. l. anadyrensis, breeds in the Anadyr River basin, Chukotka, Russia, and is morphologically distinct from menzbieri and baueri based on comparison of museum specimens collected from breeding areas. However, the non‐breeding distribution, migration route and population size of anadyrensis are entirely unknown. Among 24 female bar‐tailed godwits tracked in 2015–2018 from northwest Australia, the main non‐breeding area for menzbieri, two birds migrated further east than the rest to breed in the Anadyr River basin, i.e. they belonged to the anadyrensis subspecies. During pre‐breeding migration, all birds staged in the Yellow Sea and then flew to the breeding grounds in the eastern Russian Arctic. After breeding, these two birds migrated southwestward to stage in Russia on the Kamchatka Peninsula and on Sakhalin Island en route to the Yellow Sea. This contrasts with the other 22 tracked godwits that followed the previously described route of menzbieri, i.e. they all migrated northwards to stage in the New Siberian Islands before turning south towards the Yellow Sea, and onwards to northwest Australia. Since the Kamchatka Peninsula was not used by any of the tracked menzbieri birds, the 4500 godwits counted in the Khairusova–Belogolovaya estuary in western Kamchatka may well be anadyrensis . Comparing migration patterns across the three bar‐tailed godwits subspecies, the migration strategy of anadyrensis lies between that of menzbieri and baueri . Future investigations combining migration tracks with genomic data could reveal how differences in migration routines are evolved and maintained.